Accounting, Auditing, and Performance Evaluation: A Comprehensive Review - Raza, Nawed (Journal of Advanced Research in Accounting and Finance Management, 2023)
This comprehensive review explores the critical roles of accounting, auditing, and performance evaluation in contemporary financial management. Accounting, encompassing financial and managerial branches, serves as the cornerstone for recording financial transactions and producing transparent financial statements. Auditing, conducted both externally and internally, ensures accountability and compliance, maintaining trust in financial reporting. Performance evaluation, through key performance indicators (KPIs), balanced scorecards, and benchmarking, drives organizational success by measuring efficiency, effectiveness, and competitiveness. The interconnectedness of these disciplines is evident, with auditors relying on accounting data for assurance and compliance, and performance evaluation drawing from both accounting and auditing insights. Evolving trends in technology integration, sustainability reporting, regulatory changes, and data analytics shape the landscape of these fields. Block chain, AI, and ESG metrics are becoming increasingly relevant, while stricter audit regulations aim to enhance audit quality. In conclusion, organizations that prioritize accounting, auditing, and performance evaluation gain a competitive edge, fostering financial stability, risk management, and adaptability in today's dynamic business environment. These disciplines remain pivotal in facilitating informed decision-making and ensuring transparency and accountability in financial management.